PERKAWINAN LINTAS IMAN DITINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Putri Tjandra, Odelia Christy; Hasugian, Kevin Kusumaatmaja (Res Nullius Law Journal, 2023)
In general, every human being will appearing the desire to live side by side with another, to bulid for a hapy family. Based on one belief and same decisions that they want to educate with their descendants with good religious. Whereas, not a few copules who get married with diffrent beliefs. It cannot be denied that there is no boundaries and limit to build a social contact and interaction between them. Moreover, there are a problems in the regulation and recording of whether or not an interfaith marriage is legal, the procedures that must be prpeared well and the substance of the marriage law which does not provide spaces for copules to carry out marriages of diffrent religions. The result of the research used by empirical juridical which is data are obtained based on empirical and juridical aspects. This research approach, and the reasearch’s team uses a qualitative approach because of the problems related to humans are fundamentally based on our observations. The purpose of writing this journal is to find out how Indonesia is able to regulate interfaith marriage in terms of positive law, and islamic law. Second, as well as what strategies are carried out by prospective copules who want to carry out interfaith marriage.